Blockade of endothelial adenosine receptor 2 A suppresses atherosclerosis in vivo through inhibiting CREB-ALK5-mediated endothelial to mesenchymal transition - Yongfeng Cai; Yaqi Zhou; Qiuhua Yang; Jiean Xu; Qingen Da; Qian Ma; Dingwei Zhao; Tammy Lu; Ha Won Kim; David Fulton; Xuejun Jiang; Neal L. Weintraub; et al. (Elsevier, 2024)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide, and morbidity and mortality rates continue to rise. Atherosclerosis constitutes the principal etiology of CVDs. Endothelial injury, inflammation, and dysfunction are the initiating factors of atherosclerosis. Recently, we reported that endothelial adenosine receptor 2 A (ADORA2A), a G protein-coupled receptor (GPCR), plays critical roles in neovascularization disease and cerebrovascular disease. However, the precise role of endothelial ADORA2A in atherosclerosis is still not fully understood. Here, we showed that ADORA2A expression was markedly increased in the aortic endothelium of humans with atherosclerosis or Apoe-/- mice fed a high-cholesterol diet. In vivo studies unraveled that endothelial-specific Adora2a deficiency alleviated endothelial-to-mesenchymal transition (EndMT) and prevented the formation and instability of atherosclerotic plaque in Apoe-/- mice. Moreover, pharmacologic inhibition of ADORA2A with KW6002 recapitulated the anti-atherogenic phenotypes observed in genetically Adora2a-deficient mice. In cultured human aortic endothelial cells (HAECs), siRNA knockdown of ADORA2A or KW6002 inhibition of ADORA2A decreased EndMT, whereas adenoviral overexpression of ADORA2A induced EndMT. Mechanistically, ADORA2A upregulated ALK5 expression via a cAMP/PKA/CREB axis, leading to TGFβ-Smad2/3 signaling activation, thereby promoting EndMT. In conclusion, these findings, for the first time, demonstrate that blockade of ADORA2A attenuated atherosclerosis via inhibition of EndMT induced by the CREB1-ALK5 axis. This study discloses a new link between endothelial ADORA2A and EndMT and indicates that inhibiting endothelial ADORA2A could be an effective novel strategy for the prevention and treatment of atherosclerotic CVDs.